Influence Factors in Land Use of Wan Abdul Rachman Forest Park - Simarmata, Gita Bahana; Qurniati, Rommy; Kaskoyo, Hari (Jurnal Sylva Lestari, 2018)
Forest land use is an activity which is committed by the community near the forest to fulfill the needs of their life. This research intended to determine factors that influence land utilization in Wan Abdul Rachman Forest Park. Utilization of forest land was assumed as the number of plant species that planted in forest land. The analysis of this research used multiple linear regressions to test factors that influence the number of plant species. This research showed that the number of plant species was influenced by duration of farming and land area size. It was revaled that longer duration of farming and larger community's land would increase the number of plant species that has economic values. Keywords: land area, number of plant species, duration of farming, utilization of forest land.